Ultrathin MOF nanosheet-based resistive sensors for highly sensitive detection of methanol. Issue 82 (26th September 2022) - Dai, Fangna; Cui, Xiaoya; Luo, Yuwei; Zhang, Dongzhi; Li, Nanjun; Huang, Ying; Peng, Yongwu
Abstract : Ultrathin anionic metal–organic framework (MOF) nanosheets used as active materials have been fabricated as a resistive sensor, which exhibits a high sensitivity for methanol at sub-ppm level at room temperature. Abstract : Sensors with high-sensitivity for resistive methanol gas detection are highly desirable. Herein, we report newly designed ultrathin anionic metal–organic framework (MOF) nanosheets (NSs), with an average thickness of 10 nm and an electrical conductivity of 3.77 × 10 −4 S cm −1 . The ultrathin MOF NSs can be used as the active material in an electronic methanol gas sensor, which exhibits high sensitivity toward methanol gas at room temperature, i.e., high R air / R gas (363.2 at 100 ppm), fast gas response/recovery speed (6 s/2 s at 20 ppm), long-term stability, and superior cross-selectivity against other interfering gases.